The Analysis of Wafe Refraction using SWAN Model - Sujantoko Sujantoko (IPTEK The Journal for Technology and Science, 2009)
Wave simulation is important problem in nearshore coastal design process. Determination of proper wave parameter will provide reliable and accurate design, therefore modeling usually needed to simulate this process where numerical model is the right choice because of its cost is cheaper and the result is quite accurate. SWAN (Simulating Wave Nearshore) is numerical model that already used widely to simulate wave in coastal area. In this research we analyze wave refraction by SWAN model with any coastal profile (m) i.e. 0,01 , 0,03 and 0,05. This simulation also applied in the real problem at Tegal port in Central Java Province. According to the result of this model we find that in the same direction, height, and period, the height of wave break will increase as the coastal slope increase. These problems arise due to decreasing in value of db/Hb that means the peak wave is become steep. Coastal Profile affect the wave height (duo to refraction) about 2%-34%. The jetty at Tegal Port induce the wave height big alteration at dock pond (228,91%) at wave direction 30o, while at groove, back and head of the jetty, wave reduction reach until 12,96% ; 0,02% and 3,55% at incoming wave direction 45o. In the head of the jetty, the wave almost doesn’t being reduced because diffraction and wave reflection doesn’t have significant effect.